The Effectiveness of the Sale and Purchase Agreement for Online Business People in Bone Regency - Yusriadi Yusriadi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2019)
The influence of globalization and economic growth in business activities, the existence of buying and selling rules is a new paradigm for the implementation of the law in Indonesia. In business activities, it is never separated from the problem of an agreement. Actually, buying and selling agreements can be made online that are made on the basis of mutual trust. But the fact is that if a problem occurs in the future, we cannot do much to solve is related to the problem of the agreement that has been done before. This research was conducted in Bone Regency, South Sulawesi Province. This study uses a normative approach combined with a sociological approach to see the reality in the field. The research informants consisted of 10 online traders and 10 consumers, data collection techniques used questionnaire and interview systems. Based on the results of research on the effectiveness of buying and selling agreements by online traders in Bone Regency, they are considered effective. The factors that influence the effectiveness of buying and selling agreements by online traders are knowledge, trust, and habits